Agustín Cárdenas y las formas del silencio - Nancy Morejón (Caravelle)
In this aesthetic meditation, Nancy Morejón connects the forms of silence created by the sculptor Agustín Cárdenas with time, memory and Caribbean space, defining them as a part of West Indian speech.